The Effect of Managerial Capabi lities and Accounting Knowledge of MSMES on Msme Performance in Sinjai District - Alia Rezki Amalia (JEKAMI Journal of Accounting, 2021)
This study aims to determine the effect of managerial ability and accounting knowledge of MSME actors on MSME performance in Sinjai Regency. The type in this research is explanatory quantitative. The processed data by the result of distributing questionnaires to MSME actors with a sample of 100 respondents. The research instrument in this study used the Likert scale method. The data analysis technique in this research is multiple linear regression. The results of this study show that data by using statistical calculations through the application of the Statistical Package for the Social Science (SPSS) version 25 shows that (1) the managerial ability of MSME actors has an effect and is significant on MSME performance, ( 2) MSME actors' accounting knowledge has no effect and significantly to the performance of MSMEs, (3) managerial ability and accounting knowledge together have a significant and significant effect on the performance of MSMEs.